2012
DOI: 10.1038/leu.2012.319
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of 11q23 aberrations in adult acute myeloid leukemia and the role of allogeneic stem cell transplantation

Abstract: The clinical features and outcomes of 148 patients with acute myeloid leukemia (AML) and 11q23 chromosomal abnormalities were compared with those of 2640 patients with non-11q23 AML. Patients with t(9;11)), t(6;11), or other 11q23 balanced translocations [t(11;v)(q23;v)] presented at a younger age and with higher percentage of bone marrow blasts. Unbalanced 11q23 abnormalities were commonly associated with deletions of chromosomes 5q, 7q and/or complex karyotypes. In multivariate analysis, when compared to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 36 publications
6
35
0
1
Order By: Relevance
“…[27] and Sucic et al [28] stressed on the point that not only t(15;17) is restricted to M3, but also practically, all M3 patients had this translocation at DNA levels even if karyotypically normal. Consistent with Grimwade and Solomon [29] and Chen et al [30] , this rearrangement is firmly established as remarkably APL associated cytogenetic abnormality classified among favorable group. Moreover, Chauffaille et al [31] [32] and…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…[27] and Sucic et al [28] stressed on the point that not only t(15;17) is restricted to M3, but also practically, all M3 patients had this translocation at DNA levels even if karyotypically normal. Consistent with Grimwade and Solomon [29] and Chen et al [30] , this rearrangement is firmly established as remarkably APL associated cytogenetic abnormality classified among favorable group. Moreover, Chauffaille et al [31] [32] and…”
Section: Discussionsupporting
confidence: 69%
“…In two studies done by Chen et al [30] and Grȍschel et al [36] , all patients with this rearrangement died prior to chemotherapy which confirmed the bad prognostic value of 11q23. The WHO 2008 stated that most AML cases with 11q23 abnormalities express the NG2 homologue in consistence with results in our study Regarding EVI1 (3q26) rearrangements, 3/41 (7.3%) cases showed positive signals; the first one was M1/ M2, the second was M4 and the last one was M5, they showed a characteristic multilineage dysplasia especially in megakaryocytes, this observation was confirmed by WHO 2008 which reported a peripheral blood with hypogranular neutrophils with a pseudo PelgerHuet anomaly, and a BM with morphologic multilineage dysplasia.…”
Section: Discussionmentioning
confidence: 71%
“…A more favourable outcome has been reported in patients receiving an allogeneic hematopoietic-stem-cell transplantation (alloHSCT) in an early phase, although previous series are based on limited data due to the low frequency of MLL-r AML and the heterogeneity of the disease 11,13,16,17 . Therefore, larger studies are needed to improve the knowledge of alloHSCT for these leukemias.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have however shown that the prognosis of MLL-r AML is heterogeneous, highly dependent on the 11q23 fusion partner, with a long-term overall survival (OS) ranging from 0 to 45% [11][12][13] . The most frequent translocation, t(9;11)(p22;q23) found in nearly 30-40% adults with 11q23/MLL rearranged AML 13, 14 , is associated with the best prognosis, in contrast with most of the remaining 11q23/MLL rearrangements, which are usually associated with a poor prognosis 13,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Such an endeavor might prove to be challenging, especially when considering that clinical, biological and genetic characteristics pertinent to the disease, as well as patient-related characteristics such as age, performance status and a high HCT comorbidity index, among others, are likely to influence the overall outcomes following allo-HCT in patients with AML. [24][25][26][27][28] A previous singleinstitution study comparing a myeloablative regimen of i.v. BU (Busulfex, Otsuka, Rockville, MD, USA; Busilvex, Pierre Fabre, Toulouse, France) plus CY (ivBUCY) with two RIC regimens of flurarabine plus i.v.…”
Section: Introductionmentioning
confidence: 99%